2023
DOI: 10.1029/2022pa004577
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Cycle Responses to Changes in Weathering and the Long‐Term Fate of Stable Carbon Isotopes

Abstract: Chemical weathering of rocks and deposits eventually provides a continuous flow of carbon and other elements to the ocean (e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 146 publications
0
7
0
Order By: Relevance
“…Greater organic carbon flux initially causes lower δ 13 C DIC but it also yields higher surface ocean pCO 2 . Similar to the carbonate weathering scenario, this enhances isotopic fractionation during marine photosynthesis, resulting in a long‐term increase in δ 13 C DIC of ∼0.2‰ (Jeltsch‐Thömmes & Joos, 2023). While the resulting signal is comparable to the observed δ 13 C trend over the past 250 kyr, the required shifts in carbonate weathering and organic carbon fluxes are quite large.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Greater organic carbon flux initially causes lower δ 13 C DIC but it also yields higher surface ocean pCO 2 . Similar to the carbonate weathering scenario, this enhances isotopic fractionation during marine photosynthesis, resulting in a long‐term increase in δ 13 C DIC of ∼0.2‰ (Jeltsch‐Thömmes & Joos, 2023). While the resulting signal is comparable to the observed δ 13 C trend over the past 250 kyr, the required shifts in carbonate weathering and organic carbon fluxes are quite large.…”
Section: Discussionmentioning
confidence: 95%
“…The overall signal (∼0.3‰) is comparable to the observed increase in mean δ 13 C between MIS 6 and 2 (Oliver et al., 2010) and MIS 5e and 1 (this paper, Bengtson et al., 2021). As detailed in Jeltsch‐Thömmes and Joos (2023), a simulated reduction in carbonate weathering results in a cascade of biogeochemical effects, starting with lower oceanic alkalinity and higher surface ocean pCO 2 . This in turn enhances isotopic fractionation during photosynthesis, resulting in lower δ 13 C of particulate organic carbon and therefore higher δ 13 C of DIC (δ 13 C DIC ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous model simulations, that included organic carbon burial, showed that interactive sediments greatly affect atmospheric CO 2 and carbon isotope amplitudes through the burial-nutrient feedback (Tschumi et al, 2011;Roth et al, 2014;Jeltsch-Thömmes et al, 2019;Jeltsch-Thömmes and Joos, 2023). Dynamic sedimentary adjustment and imbalances in weatheringburial fluxes also increase the equilibration time of atmospheric CO 2 by a factor of up to 20 to several tens of thousands of years and the resulting 𝛿 13 C perturbations take hundreds of thousands of years to recover (Roth et al, 2014;Jeltsch-Thömmes et al, 2019;Jeltsch-Thömmes and Joos, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Previous model simulations, that included organic carbon burial, showed that interactive sediments greatly affect atmospheric CO 2 and carbon isotope amplitudes through the burial-nutrient feedback (Tschumi et al, 2011;Roth et al, 2014;Jeltsch-Thömmes et al, 2019;Jeltsch-Thömmes and Joos, 2023). Dynamic sedimentary adjustment and imbalances in weatheringburial fluxes also increase the equilibration time of atmospheric CO 2 by a factor of up to 20 to several tens of thousands of years and the resulting 𝛿 13 C perturbations take hundreds of thousands of years to recover (Roth et al, 2014;Jeltsch-Thömmes et al, 2019;Jeltsch-Thömmes and Joos, 2023). These findings demonstrate that organic and inorganic sedimentary changes and imbalances between the weathering and burial fluxes to the consolidated sediments and lithosphere need to be considered when quantifying carbon reservoir changes of the ocean, atmosphere and land and interpreting the reconstructed changes in CO 2 , isotopes, and nutrients over glacial cycles.…”
Section: Introductionmentioning
confidence: 99%